2013
DOI: 10.1155/2013/740573
|View full text |Cite
|
Sign up to set email alerts
|

Prooxidant Mechanisms in Iron Overload Cardiomyopathy

Abstract: Iron overload cardiomyopathy (IOC), defined as the presence of systolic or diastolic cardiac dysfunction secondary to increased deposition of iron, is emerging as an important cause of heart failure due to the increased incidence of this disorder seen in thalassemic patients and in patients of primary hemochromatosis. At present, although palliative treatment by regular iron chelation was recommended; whereas IOC is still the major cause for mortality in patient with chronic heart failure induced by iron-overl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 67 publications
(68 reference statements)
1
33
1
1
Order By: Relevance
“…A biological plausible mechanism for the association between elevated ferritin concentration and transferrin saturation and prolonged QT interval may be iron induced oxidative stress via the Fenton reaction(Broedbaek et al , ; Poulsen et al , ). Free radicals causing oxidative stress have been suggested to cause damage of proteins and DNA, including mitochondrial DNA in the myocardium (Oudit et al , ; Lekawanvijit & Chattipakorn, ; Murphy & Oudit, ; Cheng & Lian, ). Also, the accumulation per se of iron in the myocytes may impair myocyte function(James, ; Cecchetti et al , ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A biological plausible mechanism for the association between elevated ferritin concentration and transferrin saturation and prolonged QT interval may be iron induced oxidative stress via the Fenton reaction(Broedbaek et al , ; Poulsen et al , ). Free radicals causing oxidative stress have been suggested to cause damage of proteins and DNA, including mitochondrial DNA in the myocardium (Oudit et al , ; Lekawanvijit & Chattipakorn, ; Murphy & Oudit, ; Cheng & Lian, ). Also, the accumulation per se of iron in the myocytes may impair myocyte function(James, ; Cecchetti et al , ).…”
Section: Discussionmentioning
confidence: 99%
“…Also, the accumulation per se of iron in the myocytes may impair myocyte function(James, ; Cecchetti et al , ). Furthermore, oxidative stress may cause low grade inflammation(Cheng & Lian, ) leading to fibrosis by activating myocardial macrophages and fibroblasts(Oudit et al , ; Cheng & Lian, ). Lastly, in animal models, increased iron stores have been shown to increase PR interval, QRS interval and QT interval(Obejero‐Paz et al , ).…”
Section: Discussionmentioning
confidence: 99%
“…The activity of mitochondrial Fe/S cluster proteins is reduced in failing hearts, an effect attributed to the lack of an Fe/S cluster centre . On the other hand, clinical data and evidence from animal models with specific genetic defects have suggested that myocardial iron overload or accumulation of iron in the mitochondria can induce or exacerbate cardiomyopathy, presumably as a consequence of ROS‐dependent mechanisms. The question of whether iron accumulates in the mitochondria of failing hearts due to a shared aetiology, such as hypertension or myocardial infarction, has not been examined.…”
Section: The Impact Of Iron Deficiency In Heart Failure: a Co‐morbidimentioning
confidence: 99%
“…High levels of oxidative stress can predispose to diseases and rapid ageing [17] and should be taken into consideration for husbandry, health care and more globally ex-situ conservation of endangered species like the BR. Oxidative stress is reported to worsen iron overload syndromes like iron overload cardiomyopathies in humans [65], which themselves favour reactive oxygen metabolite formation and thus oxidative stress increase [17]. IOD could then be self-sustained through the oxidative stress induced, leading to a vicious circle.…”
Section: Discussionmentioning
confidence: 99%